Cosmology using numerical relativity - Josu C. Aurrekoetxea; Katy Clough; Eugene A. Lim (Living Reviews in Relativity)
Abstract This review is an up-to-date account of the use of numerical relativity to study dynamical, strong-gravity environments in a cosmological context. First, we provide a gentle introduction into the use of numerical relativity in solving cosmological spacetimes, aimed at both cosmologists and numerical relativists. Second, we survey the present body of work, focusing on general relativistic simulations, organised according to the cosmological history—from cosmogenesis, through the early hot Big Bang, to the late-time evolution of the universe. We discuss the present state-of-the-art, and suggest directions in which future work can be fruitfully pursued.